1971
DOI: 10.1111/j.1600-0609.1971.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucopoietic Properties of Four Different Androgenic Hormones in Irradiated Rats

Abstract: The bone marrow of irradiated rats was used to study the leucopoietic properties of 4 androgenic hormones; nortestosterone (Durabolin®), hedydroisoandrosterone (DHA), testosterone propionate and fluoxymesterone. Data were analysed to compare results in both sexes, various dosages of the hormones and differences between prophylactic and therapeutic treatment. According to the results, it was concluded that the androgenicity or anabolic property of a given hormone plays a role in its leucopoietic effect which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It has been reported that AR broadly expresses in neutrophil-lineage cells from the myeloblast stage to the mature neutrophil stage with no difference in the pattern of AR expression between male and female (16). Androgen was found to stimulate proliferation of committed erythrocytic and granulocytic precursors in vitro (17)(18)(19)(20), and accelerate recovery of leukocytes after radiation or chemotherapy (21)(22)(23)(24)(25). Clinical observations with androgens in the treatment of aplastic anemia (26,27), Fanconi's anemia (28,29), and during therapy with myelosuppressive agents (30,31) suggest that androgen might increase neutrophil production.…”
mentioning
confidence: 99%
“…It has been reported that AR broadly expresses in neutrophil-lineage cells from the myeloblast stage to the mature neutrophil stage with no difference in the pattern of AR expression between male and female (16). Androgen was found to stimulate proliferation of committed erythrocytic and granulocytic precursors in vitro (17)(18)(19)(20), and accelerate recovery of leukocytes after radiation or chemotherapy (21)(22)(23)(24)(25). Clinical observations with androgens in the treatment of aplastic anemia (26,27), Fanconi's anemia (28,29), and during therapy with myelosuppressive agents (30,31) suggest that androgen might increase neutrophil production.…”
mentioning
confidence: 99%